Actualization of the Polissian Dialect in the Prose Texts of Olena Lototska (Linguostylistic Studies, 2022)
The issue of literary and dialectal language interaction is a topical issue of theoretical and practical importance in modern linguistics. One of its aspects is the use of dialects in the artistic texts that influences the dynamics of style and general literary norms through the aesthetic function of the language. The elucidation of the author's individual features of presenting the conversational language elements in the artistic texts contributes to creating a holistic picture of the tendencies in dialect-literary vocabulary interaction, in general, and modern trends in the development of language and literature, in particular.The interest of the writers of Polissya to the folk language clearly manifested itself in the 80–90s of the twentieth century. The authors, the bearers of the Ukrainian dialects, began to seek self-expression in the artistic word, actualizing the features of the local dialect in their texts. Olena Lototska supported the trend of creating literary works combining literary language and dialect elements.The source of the research is prose texts from Olena Lototska’s debut book. The purpose of the study is to trace multilevel features of the Polissian  dialect in the works of Olena Lototska.The analyzed texts convincingly testified that O. Lototska, writing her works predominantly in the Ukrainian literary language, reproduces various levels of the Polissian dialect peculiarities with varying degrees of frequency and sequence. At the phonetic level, the writer is disposed to preserve the specificity of reflexion of the ancient and positional variants of modern vowel phonemes, differences in consonant phonemes loading, and combinatorial sound changes. At the morphological level, the most prominent dialect phenomena are those connected with the peculiarities of the substitution of the nominal parts of language and verbs. The features of the morphemic composition of adverbs are also in the focus of the study. O. Lototska also uses a lot of dialectal tokens explaining their meaning, which does not complicate the perception of the texts by an unprepared reader.Olena Lototska attempted to use certain dialect elements, or imitation of the dialect speech, in her works written in a literary language, and she did it skillfully. The texts represent the Polissian dialects in all their diversity and can be successfully used as a material for the dialect studies.
Keywords: Polissia; dialect; Polissian dialect; dialectism